Pengaruh Kemudahan Penggunaan dan Kualitas Layanan Terhadap Keputusan Pembelian pada Konsumen Muslim Pengguna Layanan E-Commerce di Kota Serang - Sutendi, Dedi; Masykuroh, Nihayatul; Rujikartawi, Erdi (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2024)
Purchasing decisions are a stage in determining a company's marketing strategy. With the advent of the internet, e-commerce has emerged as a popular trend in shopping due to its ease and practicality. Service quality factors influence consumer purchasing decisions. For e-commerce consumers, there are three components to the type of service that influence purchasing decisions: delivery service quality, application administrator service quality, and store service quality. Apart from that, many consumers want easy applications when shopping online. This study employs multiple linear regression analysis in SPSS Version 25. We collected data through a questionnaire on e-commerce consumers who lived in the city of Serang in the last 3 months. The research results show that service quality and ease of use partially influence purchasing decisions. Simultaneously, service quality and ease of use influence purchasing decisions. Purchasing decisions have a very strong correlation with service quality and ease of purchase among e-commerce consumers in the city of Serang.